2017
DOI: 10.1038/s41529-017-0015-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and electrochemical conditions within stress corrosion and corrosion fatigue cracks

Abstract: In the area of environment assisted cracking, literature aimed at understanding the chemical and electrochemical conditions at/ near the crack tip establishes that the crack tip is occluded and not well represented by bulk conditions. A review of the relevant literature, both modeling and experimental, is presented here and shows that crack tip conditions are determined by the balance between high metal ion concentrations resulting from crack tip anodic reactions and subsequent hydrolysis, mass transport (incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Over the past decade, many researchers have investigated different aspects of the effect of machining on SCC and pitting susceptibility of ASS. It is well-reported that a higher magnitude of RS makes the surface more susceptible to SCC occurrence [28][29][30][31][32]. On the other hand, recent investigations reported that tensile RS has no direct effect on SCC of ASS made by manufacturing methods such as hot or cold rolling and it only makes the surface more active compared to annealed specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, many researchers have investigated different aspects of the effect of machining on SCC and pitting susceptibility of ASS. It is well-reported that a higher magnitude of RS makes the surface more susceptible to SCC occurrence [28][29][30][31][32]. On the other hand, recent investigations reported that tensile RS has no direct effect on SCC of ASS made by manufacturing methods such as hot or cold rolling and it only makes the surface more active compared to annealed specimens.…”
Section: Introductionmentioning
confidence: 99%
“…25,26,85 Moreover, the crack chemistry can be far more acidic and reach pH down to 2-3 where hydrogen evolution reactions then dominate. 99 The oxygen concentration at the crack tip usually depletes quite rapidly which promotes anodic activities, with the crack wall and crack mouth becoming cathodic sites. 99 When the crack gets sufficiently long, the IR drop between the crack tip and the free surface where more electrolyte is available, can reach high values, so that the crack tip is practically disconnected from the electrolyte volume.…”
Section: Propensity To Scc and Factors Controlling Cracking And Corrosionmentioning
confidence: 99%
“…99 The oxygen concentration at the crack tip usually depletes quite rapidly which promotes anodic activities, with the crack wall and crack mouth becoming cathodic sites. 99 When the crack gets sufficiently long, the IR drop between the crack tip and the free surface where more electrolyte is available, can reach high values, so that the crack tip is practically disconnected from the electrolyte volume. 99 A site-specific corrosion cell, with the crack tip forming the anode and the crack walls at some distance behind the crack tip forming the cathode, is established, both favoring metal dissolution at the crack tip and also producing atomic hydrogen near the crack tip at some distance to it at the crack walls.…”
Section: Propensity To Scc and Factors Controlling Cracking And Corrosionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not unlikely that several of these mechanisms occurs simultaneously and affect one another, as suggested by Najjar et al [10]. In the vicinity of the crack tip the pH is low and the dominating cathodic reaction is proton reduction [11]. This results in hydrogen evolution and diffusion ahead of the crack tip, promoting conditions for local embrittlement [9,10].…”
Section: Introductionmentioning
confidence: 96%